Mengapa Siswa Mau (atau Tidak Mau) Kuliah? Peran Orang Tua, Motivasi, dan Kesenjangan Sosial: dukungan orang tua, motivasi intrinsik, pendidikan tinggi, kesenjangan pendidikan, fenomenologi - Zulimi, Zulimi; Trisnawati, Ema; Sapala, Silpanus Dian; Hardayu, Audisty Prana; Wahyuningsih, Devi; Feriansyah; Magisa, Nurul Septya; Puspitasari, Nindy (Lembaga Dongan Dosen, 2025)
This study aims to analyze the dynamics of parental support, intrinsic motivation, and social factors influencing high school students' interest in pursuing higher education. Using a phenomenological qualitative approach, the research was conducted in Pontianak City (urban area) and Kubu Raya Regency (rural area), involving 100 students, parents, and guidance counselors through in-depth interviews, focus group discussions (FGDs), and observations. The findings reveal that students in urban areas show a higher interest in pursuing higher education (76%) compared to those in rural areas (48%), with parental support being the dominant factor (82% vs. 30%). Additionally, gender differences were identified, with female students being more motivated to attend college (88% in urban areas, 56% in rural areas), while male students in rural areas tend to prefer working (62%). The main obstacles include financial constraints (78% in rural areas) and limited access to information (64% in rural areas).These findings highlight the importance of policy interventions focused on improving access to information and financial support, particularly in rural areas, as well as strengthening the role of guidance counselors in supporting students. This study contributes to stakeholders in designing more effective strategies to promote educational equity.